Genetic association between the APOE ε4 allele, toxicant exposures and Gulf war illness diagnosis - L Abdullah; A Nkiliza; D Niedospial; G Aldrich; G Bartenfelder; A Keegan; M Hoffmann; M Mullan; N Klimas; J Baraniuk; F Crawford; M Krengel; et al. (BMC, 2023)
Abstract Introduction Exposure to nerve agents, pyridostigmine bromide (PB), pesticides, and oil-well fires during the 1991 Gulf War (GW) are major contributors to the etiology of Gulf War Illness (GWI). Since the apolipoprotein E (APOE) ε4 allele is associated with the risk of cognitive decline with age, particularly in the presence of environmental exposures, and cognitive impairment is one of the most common symptoms experienced by veterans with GWI, we examined whether the ε4 allele was associated with GWI. Methods Using a case-control design, we obtained data on APOE genotypes, demographics, and self-reported GW exposures and symptoms that were deposited in the Boston Biorepository and Integrative Network (BBRAIN) for veterans diagnosed with GWI (n = 220) and healthy GW control veterans (n = 131). Diagnosis of GWI was performed using the Kansas and/or Center for Disease Control (CDC) criteria. Results Age- and sex-adjusted analyses showed a significantly higher odds ratio for meeting the GWI case criteria in the presence of the ε4 allele (Odds ratio [OR] = 1.84, 95% confidence interval [CI = 1.07-3.15], p ≤ 0.05) and with two copies of the ε4 allele (OR = 1.99, 95% CI [1.23-3.21], p ≤ 0.01). Combined exposure to pesticides and PB pills (OR = 4.10 [2.12-7.91], p ≤ 0.05) as well as chemical alarms and PB pills (OR = 3.30 [1.56-6.97] p ≤ 0.05) during the war were also associated with a higher odds ratio for meeting GWI case criteria. There was also an interaction between the ε4 allele and exposure to oil well fires (OR = 2.46, 95% CI [1.07-5.62], p ≤ 0.05) among those who met the GWI case criteria. Conclusion These findings suggest that the presence of the ε4 allele was associated with meeting the GWI case criteria. Gulf War veterans who reported exposure to oil well fires and have an ε4 allele were more likely to meet GWI case criteria. Long-term surveillance of veterans with GWI, particularly those with oil well fire exposure, is required to better assess the future risk of cognitive decline among this vulnerable population.